Mechanical analysis of the Nb3Sn 11 T dipole short models for the High Luminosity Large Hadron Collider. (16th July 2019) - Izquierdo Bermudez, S; Nilsson, E; Bottura, L; Bourcey, N; Devred, A; Ferracin, P; Ferradas Troitino, S; Fiscarelli, L; Guinchard, M; Löffler, C; Mazet, J; Perez, J C; et al.
Abstract: For the Large Hadron Collider luminosity upgrade, two of the NbTi 8.3 T main bending dipoles will be replaced by two shorter Nb3 Sn 11.2 T dipoles to create space for the installation of collimators in the dispersion suppression region. With the aim to verify the design features, several 2 m long 11 T models have been constructed and tested at CERN. During the fabrication and assembly of, so far, seven single and two double aperture short model magnets, several challenges were identified and tackled. These include reproducibility in coil fabrication and assembly procedure, as well as control of mechanical stresses in the conductor and surrounding structure. In order to limit coil over-compression and improve reproducibility, the cable insulation was re-optimized. In addition, a review of the collaring procedure of the 11 T magnet was launched with the goal of reducing the risk of conductor degradation due to excessive stress. In this paper, the main fabrication and assembly steps are described, including the description of the actions taken to resolve the identified weakness.